LEO Multi-Satellite Coordination and Satellite-Ground Coordination Remote Sensing Communication and Computation Integration Technology - Zhongyuan JIANG; Sen WANG; Qizhou WANG; Xiangyong CAO; Xingsong HOU; Lei LEI; Dongwei SUN; Xinghua LI; Jianfeng MA (天地一体化信息网络)
Firstly, the current situation of satellite remote sensing, communication, and computing systems was systematically analyzed, and the real-time remote sensing dilemma existing in the traditional satellite remote sensing systems and the satellite remote sensing communication integrated system architecture was deeply analyzed.Secondly, a multi-satellite and satellite-ground coordination integrated system architecture for satellite remote sensing, communication, and computation was put forward, and the key components and the working theories modes of the architecture were introduced in detail.Thirdly, the advantages of this architecture were demonstrated and the feasibility of key technologies was systematically clarified.Finally, the simulation and analysis method based on this architecture, which could reach minute-level remote sensing tasks with high timeliness and high potential application value compared with the traditional mode, was elaborated.